COngenital heart disease and the Diagnostic yield with Exome sequencing (CODE) study: prospective cohort study and systematic review. (3rd December 2020) - Mone, F.; Eberhardt, R. Y.; Morris, R. K.; Hurles, M. E.; McMullan, D. J.; Maher, E. R.; Lord, J.; Chitty, L. S.; Giordano, J. L.; Wapner, R. J.; Kilby, M. D.; ,
ABSTRACT: Objective: To determine the incremental yield of antenatal exome sequencing (ES) over chromosomal microarray analysis (CMA) or conventional karyotyping in prenatally diagnosed congenital heart disease (CHD). Methods: A prospective cohort study of 197 trios undergoing ES following CMA or karyotyping owing to CHD identified prenatally and a systematic review of the literature were performed. MEDLINE, EMBASE, CINAHL and ClinicalTrials.gov (January 2000 to October 2019) databases were searched electronically for studies reporting on the diagnostic yield of ES in prenatally diagnosed CHD. Selected studies included those with more than three cases, with initiation of testing based upon prenatal phenotype only and that included cases in which CMA or karyotyping was negative. The incremental diagnostic yield of ES was assessed in: (1) all cases of CHD; (2) isolated CHD; (3) CHD associated with extracardiac anomaly (ECA); and (4) CHD according to phenotypic subgroup. Results: In our cohort, ES had an additional diagnostic yield in all CHD, isolated CHD and CHD associated with ECA of 12.7% (25/197), 11.5% (14/122) and 14.7% (11/75), respectively ( P  = 0.81). The corresponding pooled incremental yields from 18 studies (encompassing 636 CHD cases) included in the systematic review were 21% (95% CI, 15–27%), 11% (95% CI, 7–15%) and 37% (95% CI, 18–56%), respectively. The results did not differ significantly when subanalysis was limited to studies including more than 20 cases, except for CHD associated with ECA, in which the incremental yield was greater (49% (95% CI, 17–80%)). In cases of CHD associated with ECA in the primary analysis, the most common extracardiac anomalies associated with a pathogenic variant were those affecting the genitourinary system (23/52 (44.2%)). The greatest incremental yield was in cardiac shunt lesions (41% (95% CI, 19–63%)), followed by right‐sided lesions (26% (95% CI, 9–43%)). In the majority (68/96 (70.8%)) of instances, pathogenic variants occurred de novo and in autosomal dominant (monoallelic) disease genes. The most common (19/96 (19.8%)) monogenic syndrome identified was Kabuki syndrome. Conclusions: There is an apparent incremental yield of prenatal ES in CHD. While the greatest yield is in CHD associated with ECA, consideration could also be given to performing ES in the presence of an isolated cardiac abnormality. A policy of routine application of ES would require the adoption of robust bioinformatic, clinical and ethical pathways. Copyright © 2020 ISUOG. Published by John Wiley & Sons Ltd.